Solvent Effects on the Ultrastructure and Chemical Composition of Cuticular Wax and Its Potential Bioactive Role Against Alternaria alternata in Pingguoli Pear - Song-jiang CHEN; Yong-cai LI; Yang BI; Yan YIN; Yong-hong GE; Yi WANG (Journal of Integrative Agriculture, 2014)
Effects of different polarity solvents on the ultrastructure and chemical composition of cuticular wax in Pingguoli pear as well as their bioactive role against Alternaria alternate were studied and the results showed that the highest wax content was extracted with chloroform, and its wax content was up to 322.2 μg cm−2. Long-chain fatty acids predominated in menthol extracts and n-alkanes were predominant in wax extracted with ether, chloroform and n-hexane. Pingguoli pear fruit surface was covered by a smooth and amorphous wax layer with small, scattered crystal. The morphology of recrystallized wax in vitro after removal with different solvents was not similar to that of the intact fruit surface. Removal of cuticular wax with various solvents significantly enhanced A. alternata infection, except for wax removed by methanol. The solvent extracts of methanol and chloroform stimulated the spore germination and mycelium growth of A. alternata, but the ether and n-hexane extracts showed antifungal activity.